The goodwill relevance in cash flow forecasting: The Portuguese case - Maldonado, Isabel (2019)
This study aims to analyse in what extent goodwill and goodwill impairment losses are relevant to the flows forecasting in Portugal. We explore the goodwill and goodwill impairments losses forecasting ability to predict cash flows using multiple linear regression models with one-year-ahead cash flows as a dependent variable in each regression model and including the goodwill and goodwill impairment losses in the independent variables. Our sample includes Portuguese companies consolidated annual reports belonging to the PSI-20 index and covers the period between 2010 and 2017. Regression results from the estimated models show that our key variable goodwill is statistically significant, indicating that the goodwill have significant predictive ability for one-year ahead cash flows being an important variable to consider by the users of financial statements in forecasting future cash flows and in making economic decisions. The reported goodwill impairment losses results reveal a significative and negative sign for its estimated coefficient. However, the estimates coefficient on goodwill is negative, raising the question whether the goodwill reported by Portuguese entities is really perceived as an "productive asset" or not.